Emerging evidence of genotype–phenotype associations of developmental and epileptic encephalopathy due to KCNC2 mutation: Identification of novel R405G - Wang, Sumei; Yu, Yejing; Wang, Xu; Deng, Xiaolong; Ma, Jiehui; Liu, Zhisheng; Gu, Weiyue; Sun, Dan (Frontiers in Molecular Neuroscience, 2022)
Developmental and epileptic encephalopathies (DEEs) have high genetic heterogeneity and DEE due to potassium voltage-gated channel subfamily C member 2 (KCNC2) mutation is not well understood because of scarce case studies. In two unrelated Chinese patients, an 11-year-old boy and a five-year-old girl, both diagnosed with global developmental delay (GDD), intellectual disability (ID) and focal unaware epilepsy characterized with electroencephalogram (EEG) of generalized spike and wave complexes, without significant brain lesions, whole-exome sequencing (WES) and electrophysiological analysis were performed to detect genetic variants and evaluate functional change of the mutant KCNC2, respectively. We identified a novel KCNC2 mutation, R405G, in both the patients and revealed the mutant is gain-of-function. All patients with previously reported mutations, V471L, R351K, T437A, and T437N, and R405G were found in multiple unrelated patients with DEE, respectively, showed consistent genotype-phenotype associations. These findings emphasize KCNC2 a causative gene for DEE and facilitate medication and prognosis in patients with DEE due to KCNC2 mutations.